2019
DOI: 10.1016/j.chempr.2018.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Regio- and Enantioselective Proton Migration from Skipped Enynes to Allenes

Abstract: A catalytic enantioselective proton migration of skipped enynes to allenes is developed. A newly identified chiral ferrocenyl phosphine ligand plays critical roles in controlling both regio-and enantioselectivity. The method offers a new concept to convert readily available and abundant feedstock hydrocarbons into high-value-added molecules by reconstituting C-H bond connectivity without relying on polar functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 138 publications
0
17
0
Order By: Relevance
“…Moreover, various naturally bioactive molecules contain ene-allene skeletons as core structures (Scheme ). Numerous methods have been developed for the synthesis of ene-allenes. The γ-substitution of propargylic alcohol derivatives with nucleophilic reagents, the isomerization of skipped enynes, and the ring-closing metathesis of 1, n -allenyne are the most straightforward routes to ene-allenes. However, these methodologies often suffer from problems of functional group compatibility because presynthesized substrates and organo-metal reagents are used in these reactions.…”
mentioning
confidence: 99%
“…Moreover, various naturally bioactive molecules contain ene-allene skeletons as core structures (Scheme ). Numerous methods have been developed for the synthesis of ene-allenes. The γ-substitution of propargylic alcohol derivatives with nucleophilic reagents, the isomerization of skipped enynes, and the ring-closing metathesis of 1, n -allenyne are the most straightforward routes to ene-allenes. However, these methodologies often suffer from problems of functional group compatibility because presynthesized substrates and organo-metal reagents are used in these reactions.…”
mentioning
confidence: 99%
“…It is noteworthy that performing the reaction with water scavengers, such as Na 2 SO 4 or molecular sieves, resulted in the loss of reactivity (entry 13). These results implied that water was essential for the current transformation [17] and trace water in reaction system was able to execute proton transfer. The amount of exogenous water was examined as well.…”
Section: Resultsmentioning
confidence: 90%
“…Gladly, when KF was used, an almost-quantitative yield of 3a with high Z -selectivity was observed, and only trace amounts of isomers were detected (Table , entry 6). These results provide evidence that the choice of base is critical for this reaction, which due to the easy isomerization of the 1,4-enyne under base conditions (see the Supporting Information for more details) . Then, several palladium catalysts were examined in this reaction, and it was found that Pd­(OTFA) 2 proved to be the best catalyst.…”
mentioning
confidence: 86%
“…Afterward, monofluorinated enynes generated through C–C bond elimination with released Pd catalyst for further catalytic steps. Isomerization of the skipped enyne 6a then can afford the enallene intermediate IV . Finally, intramolecular C–H bond activation and cyclization occurred, forming the product 7a .…”
mentioning
confidence: 99%